2018
DOI: 10.1002/pbc.26968
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib therapy for desmoid tumors in adolescent and young adult patients

Abstract: Pazopanib provides a promising, well-tolerated therapy for DT/AF in the AYA population and warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…11,12 The other clinical evidence is limited to a few prospective single-arm studies. [13][14][15] Moreover, most treatment regimens demonstrate inconsistent clinical responses, with less than 50% of patients typically responding to a given therapy. 8,13 Nirogacestat is a selective, noncompetitive, and reversible oral gamma-secretase inhibitor with preclinical data supporting NOTCHdependent inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The other clinical evidence is limited to a few prospective single-arm studies. [13][14][15] Moreover, most treatment regimens demonstrate inconsistent clinical responses, with less than 50% of patients typically responding to a given therapy. 8,13 Nirogacestat is a selective, noncompetitive, and reversible oral gamma-secretase inhibitor with preclinical data supporting NOTCHdependent inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…A phase II clinical study has shown apatinib’s encouraging efficacy for the treatment of metastatic sarcomas in adolescents and adults. 20 Pazopanib was shown to be effective in some case reports of pediatric osteosarcoma, 26 , 27 desmoid tumors 28 and synovial sarcoma. 29 However, clinical data on efficacy/safety of VEGFR-TKIs are still limited in the literature on pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Szucs et al, described a partial response in three out of eight patients with DTF and stable disease in five out of eight patients with a median PFS of 13.5 months (128). Another retrospective study in adolescents and young adults with DTF by Agresta et al reported tumor reduction after pazopanib use with only mild toxicities (Table 2) (129). One clinical trial is currently ongoing to investigate TKIs in the setting of DTF; pazopanib (NCT01876082, phase 2 study) (Table 3) (134).…”
Section: The Pi3 Kinase/akt and Mtor Signaling Pathways In Desmoid-tymentioning
confidence: 99%